EDUCATIONAL SITUATIONS (ES) AS USEFUL TOOLS FOR TEACHERS TO IMPROVE ARCHITECTURAL DESIGN STUDIO COURSES (ADSC) - Rahmane, Ali; Harket, Naim; Abbaoji, Messaoud (International Online Journal of Education and Teaching, 2022)
In today's world, the university is undergoing profound changes, and it needs digital technologies requiring new cognitive skills. New Information and Communication Technologies, computer and internet literacy, and teacher digital competence are increasingly becoming requirements for teaching. In architecture, teachers do not have tools to help them teaching better. This study subjects Educational Situations (ES) or tetrahedrons Cyber DiPL developed by Abbaoui et al. (2020) as suitable tools for teaching better architectural design studio courses (ADSC). The survey that served as the common thread is run with forty-nine (49) teachers from the institute of architecture, Ferhat Abbas University Setif 1 (Algeria). The results show that educational situation to do (ES to do), educational situation forged by experience (ES to practice) and educational situation to differentiate (ES to differentiate) are suitable tools. Furthermore, each ES related to know-how (Kh), knowledge practice (Kp) and theoretical knowledge, learned or scientific knowledge (Tk) brings out three other triangles (triangles of a didactic, of a pedagogy and of an apprenticeship). These triangles have corners dedicated to digital technologies to help teachers improve architectural design studio courses. The outcomes of this study could provide current and future teachers with valid and reliable tools to guide their teaching and awareness of ES development. These tools could be implemented in their teaching process and give them opportunities to make significant use of ES in architectural design studios.